2004
DOI: 10.4049/jimmunol.172.5.2976
|View full text |Cite
|
Sign up to set email alerts
|

The Ig-Like Domain of Tapasin Influences Intermolecular Interactions

Abstract: Presentation of antigenic peptides to T lymphocytes by MHC class I molecules is regulated by events involving multiple endoplasmic reticulum proteins, including tapasin. By studying the effects of substitutions in the tapasin Ig-like domain, we demonstrated that H-2Ld/tapasin association can be segregated from reconstitution of folded Ld surface expression. This finding suggests that peptide acquisition by Ld is influenced by tapasin functions that are independent of Ld binding. We also found that the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 63 publications
4
30
0
Order By: Relevance
“…An additional MHC class I interaction site has been suggested on the membrane proximal domain of tapasin consisting of residues 333-342 (18)(19)(20)(21). The amino acid alignment suggests that, although R333 and S341 are conserved between the two proteins, there is considerable variation between the two molecules in this region.…”
Section: Mhc Class I Binding Sites Defined On Tapasin Are Conserved Omentioning
confidence: 99%
See 1 more Smart Citation
“…An additional MHC class I interaction site has been suggested on the membrane proximal domain of tapasin consisting of residues 333-342 (18)(19)(20)(21). The amino acid alignment suggests that, although R333 and S341 are conserved between the two proteins, there is considerable variation between the two molecules in this region.…”
Section: Mhc Class I Binding Sites Defined On Tapasin Are Conserved Omentioning
confidence: 99%
“…Residues in the predicted contact site in MHC class I (e.g., T134) are essential for incorporation of MHC class I into the peptide loading complex and efficient peptide loading (13)(14)(15)(16)(17). A second interaction point between tapasin and the MHC class I H chain involves residues 333-342 in the C-terminal Ig-like domain of tapasin (18)(19)(20)(21), which are predicted to bind residues 222-229, situated in a b strand in the a3 domain of the MHC class I heterodimer (20,(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Furthermore, presentation of an H2-K b -restricted epitope derived from ovalbumin was reduced in ERp57-deficient mouse B lymphocytes (6). The tapasin C95A mutation did not affect H2-K b binding of this ovalbumin-derived peptide, but mutation of Cys-95 prevented the association of H2-L d with tapasin in human cells (7,8). Thus, the relative importance of conjugate formation for PLC assembly in mouse and human systems is ambiguous.…”
mentioning
confidence: 98%
“…Subsequently, it was suggested that amino acids 284 -401 mostly originating from exon 5 has an Ig-like structure (Mayer and Klein 2001). This was further elaborated on using homology modeling suggesting that 287 -401 has an Ig-like fold (Turnquist, Petersen et al 2004). After many crystallization attempts, the first protein crystal structure was reported of tapasin in a stable disulfide conjugate with ERp57 (Dong, Wearsch et al 2009).…”
Section: Tapasin Optimizes the Mhc-i Peptide Repertoire By Releasing mentioning
confidence: 99%